Synthesis of B-Substituted Anthracenyl and Pyrenyl Derivatives of ortho-Carborane - Akim V. Shmal’ko; Sergey A. Anufriev; Kyrill Yu. Suponitsky; Evgeniia P. Antoshkina; Igor B. Sivaev; Vladimir I. Bregadze (Inorganics)
Isomeric B-substituted anthracenyl and pyrenyl derivatives of ortho-carborane containing polycyclic aromatic substituents both in the position of the carborane cage most distant from the carbon atoms (position 9) and in the neighboring position (position 3) were synthesized by Pd-catalyzed cross-coupling of the corresponding iodo derivatives of ortho-carborane with polycyclic aryl zinc bromides. The derivative containing two pyrenyl substituents at the positions most distant from the carbon atoms of the ortho-carborane cage, 9,12-di(pyren-1′-yl)-ortho-carborane, was obtained in a similar way starting from 9,12-diiodo-ortho-carborane. The solid-state structures of the pyrene-containing derivatives 3-pyren-1′-yl-ortho-carborane, 9-pyren-1′-yl-ortho-carborane, and 9,12-di(pyren-1′-yl)-ortho-carborane were determined by single-crystal X-ray diffraction.